Participant evaluation of an inpatient occupational therapy groups programme in brain injury rehabilitation. (1st June 2017) - Patterson, Freyr; Fleming, Jennifer; Doig, Emmah; Griffin, Janelle
Abstract : Background/aim: Therapy groups are commonly used in brain injury rehabilitation yet patient perceptions of participation in groups are largely uninvestigated. This paper describes the occupational therapy groups programme at an inpatient brain injury rehabilitation unit and presents an evaluation from the patient's perspective. Methods: Participants were in patients with traumatic brain injury who participated in the groups programme and completed a customised self‐report questionnaire measuring perceptions about and satisfaction with four occupational therapy groups. Data were analysed descriptively and comparisons made between groups with a functional focus (meal preparation and community access) and an impairment focus (cognitive and upper limb) using Z scores. Results: Thirty‐five participants (30 males, five females) completed a total of 83 questionnaires. Over 90% of responses agreed or strongly agreed that working with others was enjoyable, that the groups provided feedback and individualised treatment, and were useful for them. There were no significant differences in perceptions about the functional and impairment‐focussed groups. An illustrative case example of participation in the groups programme is presented. Conclusions: Overall, consumer feedback on different aspects of the occupational therapy groups programme in brain injury rehabilitation was positive. Further in‐depth investigation of patient perceptions of groups including processes that facilitate or challenge participation is warranted.